(untitled) (Applied Biological Research, 2016)
Five varieties of rice viz., ‘Shalimar Rice-I’, ‘Jhelum’, ‘K-332’, ‘China-1039’ and ‘Pusa Sugandh’, commonly grown in Kashmirvalley were assessed for their extrusion behaviour. The rice obtained from above varieties was ground to flour and subjected to extrusion processing. The experiment was laid down in factorial completely randomized design with 3 feed moisture levels (14, 6 and 18%) and 3 barrel temperature levels (120, 140 and 160oC). The screw speed of 500 rpm was kept constant throughout the experiment. The effects of feed moisture and barrel temperature on system parameters (specific mechanical energy) product characteristics (density, expansion, water absorption index (WAI), water solubility index (WSI), texture (hardness) and colour of expanded rice snacks were studied. The study revealed that bulk density, WAI, L* value (whiteness) and hardness of snacks showed increase with increase in moisture content and decrease with increase in barrel temperature. Volume expansion ratio, WSI and a* (redness) and b* (yellowness) values showed decrease with increase in moisture and increase with rise in barrel temperature. The ogranoleptic evaluation revealed 14% moisture content and 160oC barrel temperature as most appropriate conditions for development of extruded snacks, irrespective of the variety used. Further, based on the physico-chemical and sensory attributes rice varieties ‘Shalimar Rice 1’ and ‘Jhelum’ were most suitable for development of snacks using extrusion technology.